2021
DOI: 10.1021/acs.analchem.1c01281
|View full text |Cite
|
Sign up to set email alerts
|

Developing Analytical Applications for Parahydrogen Hyperpolarization: Urinary Elimination Pharmacokinetics of Nicotine

Abstract: Nuclear magnetic resonance spectroscopy (NMR) is a valuable analytical tool with applications in a vast array of research fields from chemistry and biology to medicine and beyond. NMR is renowned for its straightforward data interpretation and quantitative properties, making it attractive for pharmacokinetic applications, where drug metabolism pathways, concentrations, and kinetics need to be evaluated. However, pharmacologically active compounds and their metabolites in biofluids often appear in minute concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The benefits and shortcomings of MS and NMR are listed in Table 1 . Nevertheless, limited by relatively low sensitivity, NMR is only appliable for metabolites of adequate concentrations [ 52 ].…”
Section: Main Metabolic Molecules Detecting Methodsmentioning
confidence: 99%
“…The benefits and shortcomings of MS and NMR are listed in Table 1 . Nevertheless, limited by relatively low sensitivity, NMR is only appliable for metabolites of adequate concentrations [ 52 ].…”
Section: Main Metabolic Molecules Detecting Methodsmentioning
confidence: 99%
“…Signals of structurally similar analytes have been found to form linear patterns in the 2D ZQ plots ([6] and Figure 2). These patterns aid identification [6,9] but the physical explanation for their formation has not been described yet. Analyte scope of the method is limited by its chemoselectivity, making it less universal than traditional NMR as it detects only analytes capable of binding to 2.…”
Section: Parahydrogen Hyperpolarized Chemosensingmentioning
confidence: 99%
“…Signal assignment is arguably the most notable limitation hindering wider adoption of the technique. Since hydride signals do not carry as much structural information as traditional NMR, the only reliable way of assigning signals has proven to be internal standard addition [4,7,9]. The most practical pulse sequence for hyperpolarized chemosensing [6], which can also be carried out as very fast experiments [20], resolves hydride signals (red in Figure 1) according to their mutual zero quantum (ZQ) frequency in the indirect dimension of 2D spectra.…”
Section: Parahydrogen Hyperpolarized Chemosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…NhPHIP-NMR chemosensing is based on the reversible binding of substrates to ac omplex of iridium with an Nheterocyclic carbene ligand, such as the Ir-IMes catalyst, together with p-H 2 and asuitable co-substrate,asillustrated in Figure 1. [28][29][30] Formation of these transient asymmetric complexes at high magnetic field allows the conversion of the singlet state originating from p-H 2 to hydrides magnetization that can be detected via NMR with enhanced sensitivity.W e have previously shown that the hydrides chemical shifts are highly sensitive to the structure of the analyte associating to the iridium complex and, therefore,can act as hyperpolarized probes to reveal the presence of specific substrates in the sample. [29] Thesame approach can be applied to detect most a-amino acids with enhanced NMR sensitivity.I twas previously demonstrated that these compounds can bind to iridium catalysts as bidentate ligands,v ia their amino-and carboxy groups.…”
Section: Introductionmentioning
confidence: 99%